The CHILES Continuum and Polarization Survey. II. Radio Continuum Source Catalog and Radio Properties - Hansung B. Gim; Min S. Yun; Nicholas M. Luber; Emmanuel Momjian; D. J. Pisano; Kelley M. Hess; Julia Blue Bird; Lucas Hunt (The Astronomical Journal)
The COSMOS H I Large Extragalactic Survey (CHILES) Continuum and Polarization survey is an ultradeep continuum imaging study of the COSMOS field conducted using the Karl G. Jansky Very Large Array. We obtained 1000 hr of L -band ( λ = 20 cm) observations across four spectral windows (SPWs; 1.063–1.831 GHz) in a single pointing and produced a confusion-limited image with an apparent rms noise of 1.67 μ Jy beam ^−1 with a synthesized beam of 5 $\mathop{.}\limits^{^{′′} }$ 5 × 5 $\mathop{.}\limits^{^{′′} }$ 0. This paper reports a 1.4 GHz radio continuum source catalog containing 1678 sources detected above 7 σ (flux densities greater than 11.7 μ Jy), identified using two independent source extraction programs applied to the Stokes I image. Resolved sources dominate at flux density S _1.4GHz ≥ 42 μ Jy. The radio spectral index for each source was derived using a power-law fit across the four SPWs, and we found that a robust spectral index measurement requires a total signal-to-noise ratio of at least 20. Comparisons with previous 1.4 GHz radio continuum surveys show good overall consistency, but evidence for a high degree of catalog incompleteness and the effects of source confusion are evident for some of the earlier studies.